Novobiocin inhibits initiation of RNA polymerase II-directed transcription of the mouse metallothionein-I gene independent of its effect on DNA topoisomerase II. - Webb, M L (1987)
The requirement for ATP hydrolysis in the initiation of RNA polymerase II (Pol II)-directed transcription and the relationship between ATP and novobiocin action led us to investigate whether novobiocin could inhibit transcription of the mouse metallothionein-I (MT-I) gene. Novobiocin inhibited the MT-I gene transcription in a fractionated rat hepatoma nuclear extract in a dose-dependent manner by direct interaction with a nuclear factor(s). This interaction prevented formation of stable preinitiation complexes but did not affect elongation of MT-I mRNA. Preincubation of the nuclear extract with ATP prevented the action of novobiocin on MT-I gene transcription. Although novobiocin is known to inhibit DNA topoisomerase II, VM-26, a specific inhibitor of this enzyme had no effect on the transcription. These results indicate that novobiocin blocks the Pol II-directed transcription by inhibiting formation of preinitiation complexes at an ATP-dependent step.